2017
DOI: 10.1590/2318-0331.011716099
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for measuring velocities in open-channel flows: perfomance evaluation of a Pitot tube compared to an acoustic meter

Abstract: Hydrometric measurements undertaken in channels with high velocities are conditioned to the particularities of the flow, which is often characterized by instantaneous fluctuations and disturbances on the free surface. In such cases, the uncertainties associated with velocity fluctuations exceed the precision offered by the instruments that are employed in conventional techniques. A reasonable accuracy of the results is therefore sufficient to accomplish the objective of the measurements. The use of devices bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…bottom and sidewalls) or the presence of turbulence volatilities. Our results, in concordance with the previous studies [21,22], showed that the application of Pitot-tube in the open channel experiments is effective but also tricky. Yet, based on the preliminary studies conducted by Henry Darcy in 1856 and the latter review by the Brown…”
Section: Resultssupporting
confidence: 93%
“…bottom and sidewalls) or the presence of turbulence volatilities. Our results, in concordance with the previous studies [21,22], showed that the application of Pitot-tube in the open channel experiments is effective but also tricky. Yet, based on the preliminary studies conducted by Henry Darcy in 1856 and the latter review by the Brown…”
Section: Resultssupporting
confidence: 93%
“…Bernoulli run-up is also referred to as the "velocity head rod" by Church and Kellerhals (1970), Carufel (1980), and Fonstad et al (2005) and is similar to the "weir stick" discussed by USBR (2001). The velocity measurement theory of Bernoulli is similar to using a pitot tube (Almeida and de Souza, 2017), without the associated challenges of (1) using and transporting potentially bulky and fragile equipment and (2) clogging from sediment or trash (WMO, 2010). However, the accuracy and precision of the Bernoulli method velocity head measurements are likely lower than pitot measurements.…”
Section: Bernoulli Run-up Methodsmentioning
confidence: 99%
“…2.2. The theoretical training also introduced citizen scientists to Open Data Kit (ODK; Anokwa et al, 2009), a freely available open-source software for collecting and managing data in low-resource settings. ODK was used with the specific streamflow measurement workflow described below.…”
Section: Citizen Scientist Evaluation (Phase 2)mentioning
confidence: 99%
“…The bath stirring rate was varied from 200 rpm to 1000 rpm with an interval of 200 rpm, and the corresponding rise in the electrolyte level within the Pitot tube’s column (i.e., was recorded five times for each bath stirring rate. Subsequently, was calculated using Equation (3) by considering as 1 [ 36 ], and plotted as a function of bath stirring rate as shown in Figure 2 b, where the bath stirring rate from 200 rpm to 1000 rpm resulted in (at 4 cm from the vortex center) from 8 cm/s to 42 cm/s, respectively. A good agreement is found between the simulated vortex velocity and the measured vortex velocity from the vortex core ( Figure 2 b).…”
Section: Modelling Of Electrolyte Vortex Flow Created By Magnetic Stirring and Determination Of Optimum Electrode Position Within The Vormentioning
confidence: 99%